The role of adhesion molecules in inflammatory bowel disease in children. Assessment of the possible risk of cardiovascular complications - Aneta Trzeciak-Jędrzejczyk; Ryszard Makosiej; Michał Kolejwa; Ewa Głowacka; Elżbieta Czkwianianc (Gastroenterology Review)
Introduction : Inflammatory bowel diseases (IBD) are chronic diseases that proceed with exacerbation and remission phases. Adhesion molecules play a significant role in inflammatory processes. The same adhesion molecules play an important role in atherogenesis. Aim : To assess the risk of atherosclerosis in IBD in children. Material and methods : The study included 40 patients with IBD (25 with Crohn’s disease – CD and 15 with ulcerative colitis – UC) aged 4–17 years. In the study group, concentrations of selected adhesion molecules (intracellular adhesion molecule – ICAM, vascular cell adhesion molecule – VCAM, E-selectin) and selected parameters of lipid metabolism in serum were assessed. Results : No statistically significant differences between CD and UC patients and in the control group, in mean values of selected adhesins were obtained. Average variable VCAM was significantly lower in patients with CD than in patients with UC in the active stage of the diseases. Significantly higher average levels of triglycerides (TG) and high density lipoproteins (HDL) were found in the control group than in patients with CD. Significantly higher levels of total cholesterol (CHL) and HDL were noticed in the control group patients than in the patients with UC. The HDL/CHL was significantly higher in controls than in patients with UC. Conclusions : No increased risk of developing atherosclerosis was found in children with IBD. Decreased risk in patients during exacerbation of inflammatory bowel disease was revealed, which may result from malnutrition typical for acute disease phase.